MAGNESIUM SULPHATE IN THE PROPHYLAXIS AND TREATMENT OF ECLAMPSIA - Noor, Shehla; Halimi, Mussarat; Faiz, Nasreen Ruby; Gull, Fouzia; Akbar, Nasreen (Journal of Ayub Medical College Abbottabad, 2004)
Background: Magnesium Sulphate is considered to be the agent of choice for the control of eclamptic seizures in pregnant women. Our objectives were to determine frequency of eclampsia and pre-eclampsia in our unit and to determine the effect of initial loading dose of magnesium sulphate on maternal and fetal outcome. Methods: This study was carried out in Department of Gynaecology at Lady Reading Hospital, Peshawar. In the year 2000 only 133 patients received magnesium sulphate out of 228 cases of eclampsia and pre eclampsia due to the problems with the continuous supply of the drug. This included 53 cases of eclampsia and 80 cases of pre-eclampsia. Information regarding the dosage of magnesium sulphate labor out come, maternal and fetal outcome, side effects and complications of therapy were evaluated from hospital case records. The magnesium sulphate regimen consisted of 4 gm loading dose as 20% solution intravenously over 10-15 minutes followed immediately by 5 gm into each buttock. Dose of 5gm intramuscularly was repeated only if the patient developed convulsions. Results: Eclampsia and pre-eclampsia occurred in 1 in 25.5 and 1 in 34.4 deliveries respectively. Majority of patients received the initial loading dose of magnesium sulphate, but in 2 patients dose had to be repeated. In two patients of pregnancy induced hypertension convulsions occurred soon after delivery unheralded by any signs and symptoms of impending eclampsia. Perinatal mortality was 19 (35.8%) and 16 (20%) in eclampsia and pre-eclampsia respectively. High perinatal mortality was attributed to prematurity as only 16.98% of eclampsia and 57.5% of Pre eclampsia were more than 37 weeks. One patient of sever pre-eclampsia developed postpartum hemorrhage and acute renal failure, but she recovered while another one developed sudden postpartum collapse immediately after delivery and died due to cerebrovascular accident. 8 patients of eclampsia died despite intensive management. All of them were referred from periphery with history of multiple fits and were brought in a serious state. Conclusion: Frequency of eclampsia and pre-eclampsia is high in this region with high perinatal and maternal morbidity and mortality. Magnesium sulphate is an effective drug to prevent and control seizures. It is easy to administer and subsequent nursing is easy. Seizures usually terminate after the initial loading dose of magnesium sulphate.